EL GENERO PTYCHOMYA EN MEXICO - MULLERRIED, FEDERICO KG (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1950)
100 water samples were studied for the incidence of pectin-fermenting coliform bacteria, isolating 51 coliform strains of which only 2 fermented pectin These were classified according to their IMVIC characters as follows: 36 Escherichia coli, 3 Aerpbac
CIENC MEX
Keywords: GENERO PTYCHOMYA, MEXICO; MULTIDISCIPLINARIA; MICROBIOLOGIA; BACTERIOLOGIA